Plaster cast burns: the reality. Issue 12 (25th November 2008) - Read, J A; Ferguson, N; Ricketts, D M
Abstract : An in vivo experimental study was performed of the temperatures produced by a setting plaster cast using hot and cold water. The results confirmed a statistical difference in the temperatures reached using hot and cold water. Forearm and below knee plasters did not represent a burn risk. Lower limb cylinder casts reached sufficient temperatures to cause burns with hot water but did not remain at these temperatures long enough to pose a clinical risk.